The spellbinders : charismatic political leadership - Willner, Ann Ruth (Yale University Press, 1984)
The author examines power of charisma in political leadership and its consequences in the history of the 20th century including Gandhi, Hitler, Castro, Franklin Roosevelt, Sukarno, the Ayatollah Khomeini, and Mussolini.